2018
DOI: 10.1007/s11738-018-2734-4
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and accumulation of d-pinitol in fenugreek (Trigonella foenum graecum L.)

Abstract: This article presents changes in concentrations of d-pinitol (and other cyclitols as well as low molecular weight carbohydrates) in vegetative and reproductive organs of fenugreek (Trigonella foenumgraecum L.) during an entire plant growing period. d-Pinitol was the major cyclitol in all tested organs, representing 43-94% of total cyclitols and 2-77% of total soluble carbohydrates. The highest concentration of d-pinitol was found in pods (14-23 mg g −1 of dry weight, DW), lower in leaves and stems (5-20 and 9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Baquer et al [39] used fenugreek seed powder orally in rats and confirmed the effect of blood glucose normalization, almost comparable to that of insulin. Fenugreek is a source of DP [52]. After the addition of small traces of metals, additive effects of vanadium were found, while manganese showed additive effects with insulin in vitro in animals with diabetes.…”
Section: Cyclitols Insulin Resistance and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Baquer et al [39] used fenugreek seed powder orally in rats and confirmed the effect of blood glucose normalization, almost comparable to that of insulin. Fenugreek is a source of DP [52]. After the addition of small traces of metals, additive effects of vanadium were found, while manganese showed additive effects with insulin in vitro in animals with diabetes.…”
Section: Cyclitols Insulin Resistance and Diabetesmentioning
confidence: 99%
“…In fenugreek leaves, stems, pods and seeds d -pinitol is a major cyclitol, representing 43–94% of total cyclitols and 2–77% of total soluble carbohydrates. In dry mature seeds, both the free d -pinitol and its α- d -galactosides (mono-, di- and tri-galactosyl pinitol A) occur at the concentration 0.4–0.6% of dry mass [52].…”
Section: Cyclitols Insulin Resistance and Diabetesmentioning
confidence: 99%
“…On the other hand, the major detected carbohydrates were sugar alcohols (close to 2%), followed by sucrose and other disaccharides. Despite most of these carbohydrates could not be clearly identified by the used analytical procedure, very recently, Lahuta et al [ 34 ] found that the most abundant sugar alcohols in fenugreek seeds were d -pinitol and α- d -galactosides of d -pinitol, as well as galactosides of myo -inositol.…”
Section: Resultsmentioning
confidence: 99%
“…This high to low concentration gradient, also observed in other plant taxa by both Streeter [17] and Ford [7], may point to the translocation of d -pinitol to the upper plant nodes in order to maintain metabolism in the younger, expanding leaves. In contrast to fenugreek [18], d -pinitol accumulation seemed to follow spatial (high to low) distribution which was not dependent on plant organs, as stem and bottom leaf samples had very comparable d -pinitol concentrations. Notable concentration gradients coupled with spatial differences in gene expression further emphasize the complexity of d -pinitol accumulation and demonstrate the necessity of future studies to be conducted on a whole plant basis in order to fully understand the adaptive process that plants undergo in response to osmotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…d -Pinitol concentrations were found to be highest in upper leaf nodes and were observed to decrease over time in agreement with Ford [7] who also noted d -pinitol accumulated to higher concentrations in younger, more recently expanded leaves located at the top of the plant. More recently, d -pinitol concentration has been observed to vary spatially between different plant organs of fenugreek ( Trigonella foenum graecum L. ) [18].…”
Section: Introductionmentioning
confidence: 99%